Structure-based design of charge-conversional drug self-delivery systems for better targeted cancer therapy - Xiao, Haijun; Guo, Yiping; Liu, Hongmei; Liu, Yushi; Wang, Yumin; Li, Changqing; Císař, Jaroslav; Škoda, David; Kuřitka, Ivo; Guo, Li; Sedlařík, Vladimír (Biomaterials, 2020)
Various design and fabrication strategies of carrier-based drug delivery systems have been quickly established and applied for cancer therapy in recent years. These systems contribute greatly to current cancer treatments but further development needs to be made to eliminate obstacles such as low drug loading capacity and severe side effects. To achieve better drug delivery, we propose an innovative strategy for the construction of easy manufactured drug self-delivery systems based on molecular structures, which can be used for the co-delivery of curcuminoids and all the nitrogen-containing derivatives of camptothecin for better targeted cancer therapy with minimized side effects. The formation mechanism investigation demonstrates that the rigid planar structures of camptothecin derivatives and curcuminoids with relevant leaving hydrogens make it possible for them to be assembled into nanoparticles under suitable conditions. These nanoparticles show stabilized particle sizes (100 nm) under various conditions and tunable surface charges which increase from around -10 mV in a normal physiological condition (pH 7.4) to +40 mV under acidic tumor environments. In addition, in vivo mice experiments have demonstrated that, compared to irinotecan (a derivative of camptothecin) itself, the co-delivered irinotecan curcumin nanoparticles exhibited significantly enhanced lung and gallbladder targeting, improved macrophage-clearance escape and ameliorated colorectal cancer treatment with an eradication of life-threatening diarrhea, bringing hope for better targeted chemotherapy and clinical translation. Lastly, the strategy of structure based design of drug self-delivery systems may inspire more research and discoveries of similar self-delivered nano systems for wider pharmaceutical applications.
Keywords: léčivé přípravky; Nanoparticles; Neoplasms; nádory; Animals; lékové transportní systémy; Camptothecin; zvířata; Antineoplastic Agents; kamptothecin; protinádorové látky; Mice; Cell Line, Tumor; Pharmaceutical Preparations; Drug Delivery Systems; nádorové buněčné linie; nanočástice; myši